Differing interpretations of health care encounters: A qualitative study of non-Latinx health care providers’ perceptions of Latinx patient behaviors - Floríndez, Lucía I. (PLoS One, 2020)
INTRODUCTION: Due to provider shortages, it is probable that non-Latinx health care providers (HCPs) will treat Latinx patients. Because of this discrepancy, both providers and patients are likely to experience barriers and cultural differences during medical encounters. This article discusses select cultural factors and behaviors such as language, communication styles, and health care practices of Latinx families through the lens of their non-Latinx HCPs. The purpose of this study was to examine how non-Latinx HCPs perceive and describe certain behaviors they observe during healthcare visits with Latinx patients and families, and to illustrate how those behaviors can alternatively be interpreted as representing Latinx cultural norms. METHODS: This qualitative study used a template coding approach to examine narrative interviews conducted with 18 non-Latinx HCPs to report how they described interactions with and the behaviors of their Latinx patients. Template codes were based on well-established Latinx cultural norms (e.g., familismo, respeto, personalismo, simpatía, confianza). RESULTS: Many HCP descriptions of Latinx patient behaviors were coded into the Latinx cultural values categories (familismo, personalismo, simpatía, respeto, and confianza) by the research team. Results suggest that HCPs were not aware of how several of their patients’ behaviors may be culturally grounded, and that cultural differences between HCPs and their Latinx patients may exist. DISCUSSION: Understanding how Latinx-specific cultural norms may be exhibited by Latinx patients and their families during healthcare encounters has potential to improve providers’ understanding of patient behavior, helping to promote culturally congruent care for Latinxs.